Placental Maspin Gene Expression Pattern May Be Used to Distinguish Between Preeclampsia and Intrauterine Growth Restriction - Onalan, Gogsen; Terzi, Yunus Kasim; Tohma, Yusuf Aytac; Yurtcu, Erkan; Kuscu, Esra; Sahin, Feride Iffet; Zeyneloglu, Hulusi Bulent (Gynecology, obstetrics & reproductive medicine : GORM, 2021)
Objective: Maspin is one of the members of serin protease inhibitor superfamily, and acts as a tumor suppressor protein. Here we report maspin expression in placental tissues of preeclampsia or intrauterine growth retardation pregnancies.Study Design: Maspin expression level was analyzed by semi-quantitative RT-PCR method. For this purpose, placental tissue samples were obtained from pregnancies 13 with intrauterine growth retardation, and 6 with preeclampsia, and also 12 tissues from women without preeclampsia or intrauterine growth retardation history were included as controls. Results: Maspin expression was found to be 11-fold higher in placentas from preeclampsia patients than placentas from intrauterine growth retardation patients (p=0.036). However, there was no difference between preeclampsia and control groups (p=0.76), and intrauterine growth retardation and control groups (p=0.849).Conclusion: As far as we know this is the first study reporting expression level of maspin in placental tissues of pregnancies with intrauterine growth retardation. These findings support that molecular pathology between preeclampsia and IUGR might be different at the molecular level and maspin levels in the placenta may be used to differentiate preeclampsia from IUGR.